Alcohol: Does it make you successful? A longitudinal analysis - Patrick Keller (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
This thesis analyzes the link between alcohol consumption and labor market outcomes, such as income, employment or hazard rate of leaving unemployment. It does so by using panel data from the German Socio-Economic Panel (SOEP) forthe period 2006 until 2010. While cross-sectional methods show a positive relationship between non-abusive alcohol consumption and labor market outcomes, fixed effects methods do not confirm a causal effect of alcohol consumption on labor market outcomes. These results suggest, that the often replicated, cross-sectional finding of a positive relationship between income and alcohol consumption (alcohol income puzzle) is due to selection bias.
Keywords: 330